Relationship marketing and customer retention in a Peruvian service company - Diaz-Fuertes, Eda Grettel; Panez-Bendezú, Miguel Humberto; Vargas-Merino, Jorge Alberto (LACCEI, 2024)
The objective of this research was to identify the influence of relationship marketing on the retention of Superpet's customers. The research design was non-experimental, crosssectional and explanatory. The study population was infinite, made up of customers over 18 years of age and who use digital media to interact with the company. We worked with a non-probabilistic sample by convenience and consecutive cases, consisting of 180 customers. The technique used was the survey. The instrument used was the questionnaire, which obtained a Cronbach's alpha of 0.904, which means a high statistical reliability, and a content validation of 99% by experts. Overall, it is concluded that there is a significant relationship between the variables under study, which is contrasted with the correlation coefficient of 0.582. The goodness of fit of the model is contrasted from the R-squared statistic that corresponds to 0.339, which means that it is 33.9% explanatory, therefore, applying relationship marketing strategies is partially beneficial to ensure the continuity of customers.